Penerapan Prinsip Non-Refoulment Kepada Pengungsi Etnis Rohingnya oleh Negara Asean - Krismansia Matulessy; Lucia Charlota Octovina Tahamata; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: This study discusses the application of the principle of non-refoulement that has been agreed upon in the 1951 Convention concerning the Status of Refugees against Rohingya Ethnic Refugees by Asean Countries.Purposes of the Research: Analyzing and knowing the urgency Analyzing the application of the principle of non-refoulement to Rohingya refugees by ASEAN countries. Methods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: Non-refoulement has binding power and must be obeyed by every country in the world considering that the principle of non-refoulement has a correlation with the principle of ius congens/jus congens which is coercive and bound for every State to implement it, both countries that are directly involved in the Convention and who are not involved. The implementation of the principle of non-refoulement against the Rohingya by ASEAN has not been fully implemented effectively. This can be seen from several ASEAN countries that are not proactive in handling the problem of Rohingya refugees. ASEAN as a Regional Organization that has the authority to intervene in human rights issues in Southeast Asia cannot act effectively because it is subject to the principles of non-intervention and consensus.